2018
DOI: 10.1186/s12885-018-5058-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dual energy CT iodine imaging and standardized concentrations before and after chemoradiotherapy for esophageal cancer

Abstract: BackgroundTo compare dual energy CT iodine imaging and standardized iodine concentration before and after chemoradiotherapy (CRT) for esophageal cancer and evaluate the efficacy of CRT for EC by examining DECT iodine maps and standard CT values.MethodsThe clinical data of 45 patients confirmed by pathology with newly diagnosed esophageal cancer who underwent concurrent CRT from February 2012 to January 2017 in our department of radiology were collected. All patients underwent dual-source dual-energy CT (DECT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Similar to gastric and colorectal cancer, Ge et al [ 59 ] demonstrated a positive correlation among esophageal cancer patients between nIC and response following chemoradiotherapy based on response criteria in solid tumors (RECIST) criteria. Unlike the studies in the gastric and colorectal group [ 36 , 48 , 49 ], two studies [ 31 , 60 ] suggested that IC/nIC can differentiate between specific cancer subtypes such as squamous cell carcinoma and adenocarcinoma in the gastroesophageal junction, as well as discriminate between small bowel adenocarcinoma and primary small intestine lymphoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to gastric and colorectal cancer, Ge et al [ 59 ] demonstrated a positive correlation among esophageal cancer patients between nIC and response following chemoradiotherapy based on response criteria in solid tumors (RECIST) criteria. Unlike the studies in the gastric and colorectal group [ 36 , 48 , 49 ], two studies [ 31 , 60 ] suggested that IC/nIC can differentiate between specific cancer subtypes such as squamous cell carcinoma and adenocarcinoma in the gastroesophageal junction, as well as discriminate between small bowel adenocarcinoma and primary small intestine lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 42 , 45 , 50 , 59 ] investigated the correlation between IC measurements with pre- and post-chemo or chemoradiotherapy treatment (three studies = neoadjuvant, one study = curative). IC was correlated to pathological findings, and all studies found a positive correlation between IC measurements and pathological response or non-response, suggesting that IQ may be used in monitoring treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the optimized plan delivery is started, commonly CBCT imaging is performed to verify the patient treatment position and to visually check anatomy changes that could cause the treatment dose to deviate from the calculated dose and negatively influence the treatment outcome. This kilovoltage CBCT can additionally be used for in vivo dosimetry, based on portal imaging in so called dose-guided radiotherapy (DGRT) [54].…”
Section: Clinical Radiotherapy Workflowmentioning
confidence: 99%
“…A slider to change the PMI pseudo-monoenergetic energy (40-190 keV) in the TPS could potentially be used to optimize the image settings for delineation purposes and could even be an alternative for window levelling. Furthermore, DECT-based post processing techniques such as colored iodine maps superimposed on the CT dataset potentially improve the visibility and thus the segmentation of cancerous tissue [53][54][55]. DECT-based RED and Zeff maps can be used to perform better tissue identification and improve dose calculations, more specifically for treatments [56].…”
Section: Preclinical Researchmentioning
confidence: 99%